Pendampingan Bimbingan Membaca Al-Qur’an melalui Metode Tilawati dalam Meningkatkan Hubungan Sosial Mahasiswa: Pengabdian - M. Fatchurahman; Nova Nur A’ini; Arliansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Quran Reading Guidance for new students at IAIN Palangka Raya and 2nd and 4th semester students taking the AIK Course at Muhammadiyah University of Palangka Raya is an important effort to improve reading skills and understanding of the contents of the holy book. This activity is carried out using a private method, which provides individual attention to each participant during 20 guidance sessions at IAIN Palangka Raya and 16 guidance sessions at Muhammadiyah University of Palangka Raya, taking place from September 11 to October 6, 2024. The methods applied include a classical approach, reading and reading together. The results of the guidance show a significant increase in students' ability to read the Quran by studying together, both in terms of fluency, understanding of tajwid, and self-confidence when reading. Despite obstacles such as variations in ability levels and motivation, the application of flexible and interactive methods has succeeded in improving the quality of Quran reading. Thus, this guidance not only strengthens students' academic abilities, but also builds a solid spiritual foundation that improves social relationships.